Interferon-γ-dependent protection against Neospora caninum infection conferred by mucosal immunization in IL-12/IL-23 p40-deficient mice. Issue 32 (6th August 2018) - Ferreirinha, Pedro; Fróis-Martins, Ricardo; Teixeira, Luzia; Rocha, António; Vilanova, Manuel; Correia, Alexandra
Highlights: Immunization can boost the immune response of Il12b −/− mice against N. caninum. Antibodies alone confer limited protection against N. caninum infection. IFN-γ is vital in vaccination-induced protection against N. caninum in Il12b −/− mice. Abstract: We have recently demonstrated the effectiveness of an intranasal immunization approach against Neospora caninum infection in immunosufficient mice. Generated evidence indicated that antibodies could be mediating the observed protection. We similarly immunized IL-12/IL-23 p40 chain-deficient ( Il12b −/− ) mice, which have impaired cellular immunity, to further explore the host protective mechanism conferred by the used immunization strategy. The immunized mice presented lower parasitic burdens after intraperitoneal infection with N. caninum and also had elevated levels of parasite-specific antibodies. However, passive immunization with antibodies purified from immunized donors conferred only limited protection to infected Il12b −/− recipients. Despite their intrinsic IL-12 deficiency, the immunized Il12b −/− mice mounted a parasite-specific immune response that was mediated by interferon-γ (IFN-γ). Neutralization of IFN-γ in the immunized mice abrogated the observed protective effect of the immunization. These results show altogether that the used immunization strategy overcome the cellular immunity defect of Il12b −/− mice and conferred protection from N. caninum infection. The observed protective effect was predominantly mediated by IFN-γ and to a lesser extent but non-negligibly by IgG antibodies. These results also highlight that in a host with compromised cellular immunity, the immune response against intracellular pathogens could be markedly boosted by immunization.